The Strategy in the micro, small and medium enterprises in Quintana Roo, Mexico : a multivariate analysis (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2015)
This research aimed to determine the factors that affect the process of setting the strategy in the Micro, Small and Medium Enterprises in the state of Quintana Roo, Mexico, using multivariate and multiple regression analysis. The research is based on the positivist paradigm, causal explanatory type and based on the survey as a technique for data collection. To gather information 280 questionnaires to owners of such enterprises established in the municipalities of Othón P. Blanco, Felipe Carrillo Puerto, Solidaridad and Benito Juarez. According to the objective set and scope of this study, statistical techniques (multivariate analysis and multiple regression) were applied. The results show that the strategy in the MPyME in Quintana Roo, Mexico; it is implicit and formulated from the experience of the owners, that is, it is conceived as a cognitive process that occurs in the mind of the decision maker and is nourished by everyday learning.
Keywords: strategy; small business; multivariate analysis